1995
DOI: 10.1159/000288999
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder Limited to Pregnancy

Abstract: The relationship between obsessive-compulsive disorder and pregnancy is reviewed in the light of recent reports concerning the frequent onset and exacerbation of obsessive-compulsive disorder during pregnancy. We present the case of a young woman who developed obsessive-compulsive disorder during a pregnancy and recovered completely after delivery. Five years afterwards she is still symptom-free. Several possible explanations for this unusual occurrence are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…3 For example, it appears that contamination obsessions and washing or cleaning rituals are prevalent during pregnancy, while postpartum OCD tends to be manifested as ego-dystonic intrusive obsessional thoughts of harming the infant, accompanied by avoidance behaviors or checking rituals. 3-8 In contrast to the gradual onset of typical OCD, postpartum OCD appears to be characterized by the rapid onset of obsessional symptoms after the birth, with onset as early as the second postpartum day with a mean time to onset of 2.2 to 3.7 weeks. 7,9 OCD in pregnancy and the postpartum period often goes undiagnosed and thus untreated, resulting in adversity for the patient, her family, and the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…3 For example, it appears that contamination obsessions and washing or cleaning rituals are prevalent during pregnancy, while postpartum OCD tends to be manifested as ego-dystonic intrusive obsessional thoughts of harming the infant, accompanied by avoidance behaviors or checking rituals. 3-8 In contrast to the gradual onset of typical OCD, postpartum OCD appears to be characterized by the rapid onset of obsessional symptoms after the birth, with onset as early as the second postpartum day with a mean time to onset of 2.2 to 3.7 weeks. 7,9 OCD in pregnancy and the postpartum period often goes undiagnosed and thus untreated, resulting in adversity for the patient, her family, and the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number and severity of stressful life events generally do not differentiate individuals with OCD from individuals without OCD, childbirth is the one specific event that individuals with OCD endorse more frequently than other stressful life events (Albert, Maina, & Bogetto, 2000;Maina, Albert, Bogetto, Vaschetto, & Ravizza, 1999). Several researchers have demonstrated that, at least in a subset of vulnerable women, OCD develops or worsens during pregnancy and continues to cause distress in the postpartum period (Altemus, 2001;Diaz, Grush, Sichel, & Cohen, 1997), although several cases of OCD limited to pregnancy (e.g., Iancu, Lepkifker, Dannon, & Kotler, 1995) and the puerprium (e.g., Hertzberg, Leo, & Kim, 1997) have been documented. In their case series of 15 women who developed postpartum OCD, Sichel, Cohen, Dimmock, and Rosenbaum (1993) determined through a retrospective chart review that eight women had no previous psychiatric history, and seven had histories of either panic disorder (PD) or generalized anxiety disorder (GAD).…”
mentioning
confidence: 99%
“…Of the other available literature, Sichel and colleagues 1819 described 15 women referred to a postpartum psychiatric disorders service who had postpartum new-onset obsessions without compulsions. Iancu and colleagues 20 presented the case of a young woman who developed OCD during her only pregnancy and recovered completely after giving birth to a healthy child. Finally, Williams and colleagues 21 retrospectively examined the relationship among pregnancy, the puerperium, the premenstruum, and the course of OCD in 57 women.…”
Section: Type Of Recent Life Eventsmentioning
confidence: 99%